Mineral composition changes recorded in the sediments from a 284-m-long drill-well in central part of the Kathmandu Basin, Nepal (Journal of Nepal Geological Society, 2001)
The mineralogical study on the sub-surface obtained from drill-well JW-3, in the central part of the Kathmandu Basin was first performed by means of X-ray diffraction (XRD). The minerals detected in the sediments are quartz, feldspar, mica, smectite, chlorite, kaolinite, gypsum and calcite. The former three minerals are main constituent of the sediments and their relative proportion is over 70%. In general, the relative proportion of quartz is congruous with that of feldspar but is reverse proportion to that of mica. The clayey phyllosilicate minerals, such as smectite, chlorite and kaolinite are next dominant minerals in the sediments, and the relative proportion of these minerals shows a similar variation pattern to each other. Gypsum and calcite occur sporadically and their ratio is less than a few percentages, except in some horizons where they exceed 5%.Variation curves of relative amounts of the minerals are mainly divided into two zones, based on the variation patterns of the minerals. In Zone I below115 m depth, the variation curves of minerals show gradual cyclic patterns with low amplitude except gypsum and calcite. On the other hand, the variations of mineral contents in Zone II above 115 m depth are larger than those in the Zone I. Particularly, the variation curves of quartz, feldspar and mica show repetition of shorter cycles at 4-7 m intervals which are overlapping a longer cycle at 30 m intervals. The change in variation pattern across 115 m depth of the drill-well is similar to that of frequency of each pollen in the same sediments, which depicts the climatic variations in the Kathmandu Basin (Fujii and Sakai 2002). Hence, the mineralogical variation must reflect not only the changes of depositional environments in the Kathmandu Basin but also the climatic variations there. Similar difference of variation pattern of mineral composition in the Zone I and Zone II are also reported from the pollen analysis of the same slimes. This difference seems to be related to global climatic changes.